P113 Duodenal surveillance in familial adenomatous polyposis: adherence to the ESGE guidelines in a tertiary center. (19th June 2022) - Awadelkarim, Bidour; Charnley, Richard; Brennan, Paul; Leeds, John; Oppong, Kofi; Nayar, Manu
Abstract : Introduction: Familial adenomatous polyposis (FAP) is an autosomal dominant condition with germline mutation in the APC gene. In addition to the colonic manifestation around 50-90% of carriers develop duodenal polyps although only a minority develop duodenal cancer with a cumulative risk ranging from 4-10% by the age of 60.The ESGE guidelines recommends starting endoscopic duodenal surveillance for patients with FAP at the age of 25. 1 We aim to assess our tertiary centre experience of duodenal surveillance in patients with FAP against the ESGE guidelines published in 2019. Methodology: Retrospective study of patients with confirmed FAP from 2007–2020. We recorded if the ESGE guidance in regard to endoscopic duodenal surveillance were followed and the management of duodenal polyps if detected particularly regarding endoscopic surveillance interval, lesions identified and any interventions. Results: 44 patients with FAP were managed at our trust with a median age of 34 at the time of diagnosis and 54% female predominance. of the 28 patients eligible for gastroduodenal surveillance 71.4% (n=20) had upper GI endoscopy and the papilla was visualised in 90% (n=18). The average interval for surveillance was 3 years with the Spigelman classification clearly documented in the notes of 70% (n=14). 40% (n=8) had duodenal polyps including papillary adenomas with 10% (n=2) having high grade adenoma/invasive cancer detected during surveillance. Table 1 reports the size and the management of these polyps. Conclusion: Early detection and management of duodenal polyps in patients with FAP can have a significant impact on the patient management. Adherence to the ESGE guidelines was suboptimal in our cohort of patients but most of our experience predates the guidelines. Reference: Van Leerdam ME, Roos VH, van Hooft JE, et al . Endoscopic management of polyposis syndromes: european society of gastrointestinal endoscopy (ESGE) guideline. Endoscopy 2019;51 (09):877-895. doi:10.1055/a-0965-0605